Observations on the biology of some sciaenid fishes from Mandapam region - Jayasankar, P (Indian Journal of Fisheries, 2011)
Regression coefficients in the length-weight relationships in females and males in Johneiops sina, Johnius dussumieri and Johnius macropterus showed no significant difference and common equation is recommended in each case. In Dendrophysa russelli, separate regression equations are necessary. Relative condition factor seems to be affected by reproductive cycle. Spawning season of./, sina, J. dussumieri and J. macropterus extended from March to October. D. russelli seems to spawn round the year. Length at first maturity in J. sina, D. russelli, J. dussumieri and J. macropterus was 152,144,168 and 136 mm respectively. Monthly sex ratio departed significantly from 1:1 only in J. sina, where there was male dominance.